Gardening Therapy With Boiled Water, Ice Cubes, Chewing Gum Reduces Thirst In Ckd Patients: Literature Review. - Pakaya, Nasrun; Husain, Filsa; Zainuddin, Zainuddin (Universitas Negeri Gorontalo, 2024)
Chronic kidney failure occurs due to a failure in the body's ability to maintain metabolism and fluid and electrolyte balance resulting in uremia or retention of urea and other nitrogenous waste in the blood. The research aims to synthesize literature about gargling therapy with boiled water, ice cube therapy, and chewing gum to reduce thirst in CKD patients. The method used is content analysis with a literature search from 2020 to 2023 using the keywords Ice Cubes, gargling, chewing gum, CKD To reduce thirst by using ice there were 6 journals, 4 journals using chewing gum, and 1 journal using boiled water. All articles show that there is an effect of gargling therapy with boiled water, ice cube therapy, and chewing gum to reduce thirst in CKD patients. The literature study shows that the use of ice cubes has the most effect on reducing thirst in CKD patients, however, gargling therapy with boiled water and chewing gum are other alternatives.